Contribution of High‐shear Processing to the Compatibilization of (PP/EPR)/PE Ternary Blends. Issue 6 (24th November 2013) - Louizi, Molka; Massardier, Valérie; Cassagnau, Philippe
<x xml:space="preserve">Abstract</x> The novel compatibilization of high impact polypropylene/high density polyethylene (PP/EPR)/PE blends by high shear process leads to a typical core–shell structure, with PE core encapsulated by EPR shell within PP matrix, a decrease of the size of (PE/EPR) domains as well as an improvement of the interface being observed when increasing screw rotation speed from 300 to 600 rpm. Possible in situ formation of copolymers can be an explanation for the improved miscibility between phases. Further, the addition of only 3 wt.‐% of ethylene‐octene copolymer (EOC) to the (PP/EPR)/PE blend processed at 600 rpm increases elongation at break and impact strength by respectively 80 and 100% as EPR and EOC could play a synergetic role. This novel process offers new perspectives for lightening and recycling.<inline-graphic xlink:href="ark:/27927/pghgzc85k3" content-type="mame201300268-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />